(untitled) (Conferencea, 2023)
This article focuses on such qualities of students as initiative, activity and self-control, which allow them to build their future and activities in accordance with social needs and the sociocultural environment. The development of student self-government in higher educational institutions, analysis of the pedagogical potential of student associations and the involvement of students in social processes is relevant. However, in Uzbekistan, research in this area is carried out at an insufficiently high level, which requires a more in-depth study of students’ self-control abilities and analysis of scientific and pedagogical work related to youth problems. The article also discusses factors influencing the development of non-state higher education in Uzbekistan and the importance of forming a legal framework in this area during the transition period of educational development. It is noted that the adoption of sets of legal documents that meet international standards opens up opportunities for improving the education system in Uzbekistan and ensuring access to modern knowledge.